Desenvolvimento da capacidade de inovação na indústria farmacêutica: o caso Phytos - Ribeiro, Juliana Vale (2014)
The present research aims to analyze the development of Phytos phytomedicine innovation capacity in the last ten years. The theoretical basis for the study is related to organizational change, dynamic capabilities, organizational learning and innovation. The research strategy adopted was the case study and, for the collection of data, the semi-structured interview was used, as well as direct observation, consultation with secondary data and documents. For the analysis, the data were categorized and interpreted in the light of the theoretical reference. Evidence made it possible to identify that Phytos' development of innovation capacity required a series of strategic changes, especially in its human and technological resources, and that changes in organizational culture were also of great importance. Phytos innovation process is characterized as a systemic process, using open innovation, stimulating cooperation between research institutions and the company, as well as the development of new products with speed and flexibility. The learning processes identified were learning: doing (learning by doing), interacting (learning by interacting) and searching (learning by searching). Knowledge, the fruit of learning processes, is institutionalized through norms and procedures, preserving the memory of the organization. It is concluded that in order to achieve the capacity for product innovation, Phytos integrated individual skills to collective competencies, from managers to employees, but also built new collective skills, such as increasing the capacity of disintegration of phytocomputer A and reducing time to obtain the inputs, applying them to all phytomedicines of the company. Phytos has reconfigured its ability to develop fast and creative solutions, its ability to select and evaluate projects, as well as the ability to acquire raw material.